Waiting for the elevator [compact disc] - Berkner, Laurie (Two Tomatoes Records, 2019)
For children, every moment is about learning, growth, and development, so it's only natural that these are the themes for Laurie Berkner's new album. Intellectual development sits right next to emotional development in these interactive songs.